Model Penilaian Kinerja Rantai Pasok Hijau Agroindustri Potato Chips - Usman, Yulita Veranda; Dwi Satya, Ririn Regiana; Safitri, Daffa Adrika; Hafizah, Salma (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 12 No 4 (2024): DesemberDO - 10.24843/JRMA.2024.v12.i04.p12, 2025)
The speed and accuracy of fulfilling potato needs in the potato processing industry are needed to anticipate consumer demand. This condition is influenced by the performance of supply chain actors to meet supply needs with good quality continuously. Potatoes are a food ingredient that is widely consumed by the Indonesian people, therefore, it is very important for the potato processing industry to be able to produce quality and safe products. The large number of actors involved in the supply chain and the nature of potatoes as an agricultural product that is easily damaged and will continue to change its quality throughout the supply chain will be an obstacle in controlling the quality and quantity of its supply. The potato chips agroindustry as one of the processed products that uses potatoes as raw materials must also pay attention to its production so as not to use hazardous food additives and above the permitted threshold. Therefore, the implementation of GAP (Good Agricultural Practices) throughout the supply chain of the green potato chips agroindustry is also very important. In an effort to improve the quality of potato chips products and their productivity in a sustainable manner, it is necessary to manage the supply chain in an environmentally friendly manner (green supply chain management). Where in the supply chain activities contribute to the use of carbon footprints released from each process. Improvement/enhancement can be done based on the results of the assessment/measurement of the performance of its supply chain that considers the environment. Thus, the purpose of this study is to identify stakeholders, variables and criteria in the green supply chain of potato chips agroindustry and to develop a model for assessing/measuring its performance. Based on the assessment of the performance of the potato chips supply chain, there are two actors, namely farmer groups which are still relatively low at 77.23% and agroindustry which is classified as medium at 84.29%. Based on the assessment of performance in the procurement business process, it has a high weight in the procurement of raw materials where in the continuity of raw materials needed according to the specifications of raw materials needed by the agroindustry related to the quality of potatoes according to the demand of the agroindustry. Keywords :  Potato chips agroindustry, Performance assessment, Green supply chain, Fuzzy AHP Kecepatan dan ketepatan pemenuhan kebutuhan kentang di industri pengolahan kentang sangat dibutuhkan untuk mengantisipasi permintaan konsumen. Kondisi ini dipengaruhi kinerja pelaku rantai pasok untuk memenuhi kebutuhan pasokan dengan kualitas yang baik secara kontinu. Kentang merupakan bahan pangan yang banyak dikonsumsi oleh masyarakat Indonesia, oleh karena itu, sangat penting bagi industri pengolahan  kentang untuk dapat menghasilkan produk yang berkualitas dan aman dikonsumsi. Banyaknya pelaku yang terlibat dalam rantai pasok dan sifat kentang sebagai produk hasil pertanian yang mudah rusak dan akan terus berubah mutunya sepanjang rantai pasoknya akan menjadi kendala dalam pengendalian kualitas dan jumlah pasokannya. Agroindustri  potato chips  sebagai salah satu hasil produk olahan yang menggunakan bahan baku kentang harus pula memperhatikan produksinya agar tidak menggunakan bahan tambahan pangan yang berbahaya dan di atas ambang batas yang diperbolehkan. Oleh sebab itu penerapan GAP ( Good Agricultural Practices ) sepanjang rantai pasok agroindustri hijau  potato chips  pun menjadi sangat penting. Dalam upaya untuk meningkatkan kualitas produk  potato chips  dan produktivitasnya secara berkesinambungan harus melakukan pengelolaan rantai pasoknya secara ramah lingkungan ( green supply chain management ). Di mana dalam aktivitas rantai pasok memberikan kontribusi terhadap penggunaan  carbon footprint  yang dikeluarkan dari masing-masing prosesnya. Perbaikan/peningkatan dapat dilakukan setelah berdasarkan hasil penilaian/pengukuran kinerja rantai pasoknya yang mempertimbangkan lingkungan. Dengan demikian tujuan penelitian ini adalah mengidentifikasi  stakeholder,  variabel dan kriteria dalam rantai pasok hijau agroindustri  potato chips  serta mengembangkan model penilaian/pengukuran kinerjanya. Berdasarkan penilaian kinerja rantai pasok  potato chips  ada dua pelaku yaitu kelompok tani masih tergolong rendah  sebesar 77,23% dan agroindustri tergolong sedang sebesar 84,29%. Berdasarkan penilaian kinerja pada proses bisnis pengadaan memiliki bobot tinggi dalam pengadaaan bahan baku dimana dalam  continuitas  bahan baku diperlukan sesuai dengan spesifikasi bahan baku yang dibutuhkan agroindustri terkait mutu kentang sesuai dengan permintaan agroindustri. Kata kunci :  Agroindustri potato chips, Penilaian kinerja, Rantai pasok hijau, Fuzzy AHP